2004
DOI: 10.1161/01.cir.0000129772.26647.6f
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Microvascular Function in Obesity

Abstract: Background-Obesity is associated with an increased risk of developing microangiopathy, hypertension, and insulin resistance. We hypothesized that obesity is a primary cause of microvascular dysfunction, which may contribute to the development of these obesity-related disorders. Methods and Results-We examined microvascular function in 16 lean (body mass index Ͻ24 kg/m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
137
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(148 citation statements)
references
References 34 publications
8
137
2
1
Order By: Relevance
“…In EC‐MR–intact mice, 12 weeks of HFD‐induced obesity resulted in significant impairment of endothelium‐dependent relaxation only in females, with no effect in males (Figure 1A and 1B). These data suggest that in female mice, as in women,5, 36 there is increased susceptibility to microvessel endothelial dysfunction in the setting of obesity. HFD combined with hPCSK9 DY ‐induced hyperlipidemia was associated with endothelial dysfunction in both male and female mice (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In EC‐MR–intact mice, 12 weeks of HFD‐induced obesity resulted in significant impairment of endothelium‐dependent relaxation only in females, with no effect in males (Figure 1A and 1B). These data suggest that in female mice, as in women,5, 36 there is increased susceptibility to microvessel endothelial dysfunction in the setting of obesity. HFD combined with hPCSK9 DY ‐induced hyperlipidemia was associated with endothelial dysfunction in both male and female mice (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 73%
“…Obesity and the associated hyperlipidemia and metabolic dysfunction are well‐known risk factors for CVD 4. One of the earliest vascular consequences of these cardiometabolic risk factors is endothelial dysfunction, characterized by impaired endothelium‐dependent relaxation 5, 6, 7. Impaired vasorelaxation decreases organ perfusion capacity and can contribute to the development of hypertension, another CVD risk factor associated with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with in vitro evidence showing that insulin stimulates NO release by endothelial cells [33] and with in vivo evidence showing that insulin potentiates acetylcholine-induced vasodilatation in resistance arteries [27] and in both skin [28] and muscle [29] microcirculation. This specific effect, however, appears attenuated in insulinresistant states [34], but we have previously shown that, in these conditions [27], insulin can still improve the vascular response to ACh exploiting its hyperpolarising effect. Alternatively, insulin might lose its positive effect on acetylcholine-mediated vasodilatation, which is mainly dependent on endothelial NO synthase activation, but not the ability to preserve the endothelial cell from the negative consequences of hyperglycaemia, which is known to act mainly through oxidative stress.…”
Section: Discussionmentioning
confidence: 76%
“…Microvascular dysfunction has already been described in OB, 22 first-degree relatives of diabetic 23 and hypertensive patients, 24 polycystic ovary syndrome 25 and type 2 diabetes mellitus 17 using different methods. Our data confirmed that OW/obese, sedentary, non-smoking and normoglycemic …”
Section: Discussionmentioning
confidence: 99%